Building Digital Public Spaces for Policy Deliberation: The Role of Digital Leadership in Managing the Palembang City Government's Online Participation Platform - Endasari, Een; Mawaddah, Mawaddah; Muslim, Muslim (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The digital era has transformed the governance landscape, shifting the paradigm from hierarchical administration to more inclusive community participation. This article explores the crucial role of digital leadership in building and managing digital public spaces that serve as policy deliberation arenas for the Palembang City Government. The study analyzes how online participation platforms can be optimized to encourage constructive dialogue, input gathering, and policy drafting that is responsive to citizens' needs. Using a qualitative approach through a case study, data was collected through in-depth interviews with relevant government officials, analysis of digital policy documents, and participatory observation of platform usage. The findings show that effective digital leadership focuses not only on providing technological infrastructure, but also on establishing a digital culture, increasing the digital literacy capacity of citizens and officials, and ensuring accountability of the deliberation process. This article concludes that the success of digital public spaces for policy deliberation is highly dependent on the commitment, vision and adaptability of leaders in the digital era, which can ultimately strengthen policy legitimacy and increase public trust in governmen